Microfabrication and characterization of cylinder micropillar array electrodes - Prehn, R; Abad, L; Sanchez-Molas, D; Duch, M; Sabate, N; del Campo, F; Munoz, F; Compton, R (2011)
This work describes de fabrication, using standard microfabrication techniques, of cylindrical micropillar array electrodes. The work also describes the characterization of these electrodes using a combination of microscopy techniques, cyclic voltammetry and finite-element simulations based on the diffusion domain approach. The work shows that while micropillar array electrodes display currents consistent with the Randles- Ševčík equation at low scan rates, they afford enhanced voltammetric peak currents at higher scan rates. Not only this, but for certain micropillar geometries and densities, simulations predict that a voltammetric peak-to-peak separations below 57 mV due to thin-layer diffusion effects. The results presented in this article are in agreement with recent works by Compton and co-workers on porous and rough electrodes, and provide further evidence of the validity of the diffusion domain approach to predict and interpret mass transport controlled currents at microstructured electrodes. © 2011 Elsevier B.V. All rights reserved.